Christ’s violent crucifixion in Hebrew Scriptures and Synoptics: Its relevance to violence in South Africa - Hombana, Mphumezi (Theologia Viatorum (Sorenga), 2025)
This study explores how the crucifixion is presented in the Synoptic Gospels, framing it as a redemptive event using Hebrew Scripture. It discusses how crucifixion – a type of state-sponsored violence – becomes a representation of freedom and atonement. Attention is also given to the difficulty of explaining this theological message to a Gentile audience that is not familiar with the Hebrew Scriptures. The study uses intertextual analysis to make the case that state-sponsored violence is a widespread kind of oppression and that Jesus’ crucifixion is an example of brutality that was both politically and religiously motivated. The question is also asked how victims of systemic violence should react by drawing comparisons between Jesus’ death and other cases of state oppression. Lastly, the study explores how early Christian authors, such as the Synoptic authors, preserved the Christian faith while communicating to a Gentile audience the redemptive significance of the crucifixion.ContributionThis study bridges biblical studies and social ethics by analysing the crucifixion in the Synoptic Gospels as state-sponsored violence with theological and redemptive significance. It draws parallels between the crucifixion and systemic violence in modern South Africa, offering insights into how faith communities can respond to oppression. By utilising intertextual analysis, the study highlights the relevance of biblical narratives for addressing contemporary issues of justice and liberation.